Damage and Repair of Tall Timber Buildings - Forsthuber, Boris; Brandon, Daniel; Toumpanaki, Eleni; Vcelak, Jan; Vojnovic, Luka (Springer Tracts in Civil Engineering, 2025)
The chapter summarizes the different methods available for damage repair after water and/or fire events. Different drying methods as well as their advantages and disadvantages are discussed. This is done separately for timber framing and mass timber constructions. The section for repair after fire events points out the different steps that should be taken after a fire event. This includes methods for soot removal, cleaning but also for the removal of odour. Aside from damage repair, also methods for damage prevention, i.e. moisture monitoring methods are discussed. These sensors detect either water (leakage detection) or wood moisture content. In the last section, the importance of asset management and post-construction management is discussed.
Keywords: Fire Damage; Moisture Monitoring; Repair of Timber constructions; Water Damage